The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1016/j.physletb.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

‘Hidden’ symmetry of linearized gravity in de Sitter space

Abstract: We demonstrate that the linearized Einstein gravity in de Sitter (dS) spacetime besides the evident symmetries also possesses the additional (local) symmetry hµν → hµν + Eµν χ, where Eµν is a spintwo projector tensor and χ is an arbitrary constant function. We argue that an anomalous symmetry associated with this hitherto 'hidden' property of the existing physics is indeed at the origin of 'dS breaking' in linearized quantum gravity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, knowledge of the dS massive fields enables us to display the structure of the field theory that appears at the massless limit. Massless field theories in dS spacetime possess some peculiarities that have no analog in flat case (see for instance [16,33,34]). Having an expression for the dS massive fields permits one to determine the indecomposable representation describing the dS massless fields.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, knowledge of the dS massive fields enables us to display the structure of the field theory that appears at the massless limit. Massless field theories in dS spacetime possess some peculiarities that have no analog in flat case (see for instance [16,33,34]). Having an expression for the dS massive fields permits one to determine the indecomposable representation describing the dS massless fields.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work [1], with respect to a coordinateindependent approach based on ambient space notations, we have shown that linearized quantum gravity in dS spacetime, constructed through canonical quantization and the usual representation of the canonical commutation relations, suffers from a hitherto 'hidden' local (gauge-like) anomaly. More technically, we have shown that the classical theory besides the spacetime symmetries generated by the Killing vectors and the evident gauge symmetry, 1…”
Section: Introductionmentioning
confidence: 99%
“…in which E µν and χ, respectively, stand for a second-order differential operator (a spin-two projector tensor) and an arbitrary constant function [1]. This hitherto 'hidden' gauge-like symmetry, however, becomes anomalous x = (x 0 = H −1 tan ρ, (H cos ρ) −1 u), ρ ∈] −π 2 , π 2 [, u ∈ S 3 , in which, the graviton field hµν can be expressed in terms of the second-rank symmetric tensor spherical harmonics on the threespheres.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations